D-mannose suppresses macrophage IL-1β production - Simone Torretta; Alessandra Scagliola; Luisa Ricci; Francesco Mainini; Sabrina Di Marco; Ivan Cuccovillo; Anna Kajaste-Rudnitski; David Sumpton; Kevin M. Ryan; Simone Cardaci (Nature Communications, 2020)
Mannose is present at trace levels in blood and regulates cancer growth. Here the authors show that supraphysiological levels of mannose can also regulate macrophages, limiting their production of IL-1β and increasing resistance of mice to LPS-induced endotoxemia and DSS-induced colitis.